The relevance of the study of Central Asian literature in the aspect of postcolonialism - Akhmetova, A.; Hanayi, O.; Junisbayev, A. (Journal of Oriental Studies, 2022)
The article discusses the relevance and importance of studying the literature of the Central Asian region of the post-Soviet space in the aspect of post-colonialism, as well as the state of the implementation of literary translation work - one of the types of literary communication, cultural dialogue in this region. The author draws attention to the fact that after gaining independence from the USSR, various types of intersectoral relations developed in this region; over the past thirty years, Kazakh, Kyrgyz, Uzbek, Turkmen and Tajik literature has not been considered in a complex, interdisciplinary sphere. On the basis of the sources that determined the colonial policy carried out by the Russian Empire and then by the Soviet Union to the states of Central Asia, the ways of reflection in the literature of the transformation of postcolonial consciousness and psychology, language and culture were analyzed in the literary literature of the period of independence of the specified region. In addition, the article analyzes his contribution to improving the methodology of literary criticism of Kazakhstan, provided that comprehensive, fundamental research covering the entire literature of the period of independence of the Central Asian region is carried out, in providing the scientific community and readers with sufficient information about Kazakh, Kyrgyz, Uzbek, Turkmen and Tajik literature in the post-Soviet space, comprehensive acquaintance with literature and development domestic education. On the basis of several sources, the author’s aesthetic and ideological features and poetic searches, laid down in the modern process of development of Central Asian literature, in the transition period – in the first years of the period of independence, formed by socio-social, economic, cultural and anthropological factors and trends, are highlighted. During the research, similar literary phenomena, themes, trends in Kazakh, Kyrgyz, Uzbek, Turkmen and Tajik literature were revealed in the last thirty years and periods of creative stagnation experienced by poets and writers. In addition, the points of scientific works that studied the contemporary literature of Central Asia, related to the problems raised in the article were analyzed.